Catalyst Engineering for Electrochemical Energy Conversion from Water to Water: Water Electrolysis and the Hydrogen Fuel Cell - Peng, Lishan; Wei, Zidong (Engineering (Beijing, China), 2020)
[Display omitted] In the context of the current serious problems related to energy demand and climate change, substantial progress has been made in developing a sustainable energy system. Electrochemical hydrogen–water conversion is an ideal energy system that can produce fuels via sustainable, fossil-free pathways. However, the energy conversion efficiency of two functioning technologies in this energy system—namely, water electrolysis and the fuel cell—still has great scope for improvement. This review analyzes the energy dissipation of water electrolysis and the fuel cell in the hydrogen–water energy system and discusses the key barriers in the hydrogen- and oxygen-involving reactions that occur on the catalyst surface. By means of the scaling relations between reactive intermediates and their apparent catalytic performance, this article summarizes the frameworks of the catalytic activity trends, providing insights into the design of highly active electrocatalysts for the involved reactions. A series of structural engineering methodologies (including nanoarchitecture, facet engineering, polymorph engineering, amorphization, defect engineering, element doping, interface engineering, and alloying) and their applications based on catalytic performance are then introduced, with an emphasis on the rational guidance from previous theoretical and experimental studies. The key scientific problems in the electrochemical hydrogen–water conversion system are outlined, and future directions are proposed for developing advanced catalysts for technologies with high energy-conversion efficiency.